DOP90 The impact of spondyloarthritis and joint symptoms on health-related quality of life and fatigue in IBD: results after 20 years of follow-up in the IBSEN study. (25th January 2019) - Ossum, A; Palm, Ø; Cvancarova, M; Moum, B; Høivik, M L; ,
Abstract: Background: Patients with inflammatory bowel disease (IBD) often suffer from musculoskeletal manifestations. Health-related quality of life (HRQoL) and fatigue are known to be associated with IBD activity as well as musculoskeletal complaints. The aim was to determine whether spondyloarthritis or joint symptoms were associated with HRQoL or fatigue after 20 years of disease in the IBSEN cohort. Methods: Four hundred and seventy incident IBD patients were followed prospectively for 20 years (the IBSEN cohort) with clinical examinations and questionnaires. At the 20-year follow-up, the patients answered detailed questionnaires regarding rheumatological diagnoses and symptoms, intestinal symptoms, as well as HRQoL (the 36-item Short Form Health Survey (SF-36) and the Norwegian version of the inflammatory bowel disease questionnaire (N-IBDQ)) and fatigue (the Fatigue Questionnaire (FQ)). Linear regression analyses were used to evaluate possible associations between spondyloarthritis or joint symptoms and HRQoL or fatigue. Sex, IBD diagnosis and age were included in all the multi-variate regression models, in addition to other clinically relevant confounders. Results: In total, 441 patients (93.8%) completed the questionnaires at the 20-year follow-up. The criteria for spondyloarthritis (axial or peripheral) were fulfilled in 158 patients (35.8%), daily back pain during the previous 3 months was reported by 79 patients (18.7%) and daily joint pain by 178 patients (42.5%). In multiple regression analyses, the variables back pain and joint pain were both independently associated with lower scores in all SF-36 domains and N-IBDQ total score, and with a higher total FQ score. Spondyloarthritis was not associated with reduced scores in any of the SF-36 domains, N-IBDQ total score or higher FQ scores, when adjusted for possible confounders. Conclusions: Ongoing joint pain and back pain were both associated with poorer HRQoL and more fatigue in IBD patients 20 years after diagnosis, while spondyloarthritis did not impact HRQoL or fatigue negatively in this cohort.